Reported human infections of H9N2 avian influenza virus in China in 2021 - Tan, Min; Zeng, Xiaoxu; Xie, Yiran; Li, Xiyan; Liu, Jia; Yang, Jiaying; Yang, Lei; Wang, Dayan (Frontiers in Public Health, 2023)
Introduction The continued emergence of human infections of H9N2 avian influenza virus (AIV) poses a serious threat to public health. The prevalent Y280/G9 lineage of H9N2 AIV in Chinese poultry can directly bind to human receptors, increasing the risk of spillover infections to humans. Since 2013, the number of human cases of H9N2 avian influenza has been increasing continuously, and in 2021, China reported the highest number of human cases, at 25. Methods In this study, we analyzed the age, geographic, temporal, and sex distributions of humans with H9N2 avian influenza in 2021 using data from the National Influenza Center (Beijing, China). We also conducted evolutionary, gene homology, and molecular characterization analyses of the H9N2 AIVs infecting humans. Results Our findings show that children under the age of 12 accounted for 80% of human cases in 2021, and females were more frequently affected than males. More cases occurred in winter than in summer, and most cases were concentrated in southern China. Human-infecting H9N2 viruses showed a high level of genetic homology and belonged to the prevalent G57 genotype. Several additional α2,6-SA-binding sites and sites of mammalian adaptation were also identified in the genomes of human-infecting H9N2 viruses. Discussion Therefore, continuous monitoring of H9N2 AIV and the implementation of further measures to control the H9N2 virus in poultry are essential to reduce the interspecies transmission of the virus.